Adolescent Characters in The Matrilineal Family in Indonesia - Natsir, MHD; Suryadi, Ace; Kamil, Mustofa; Sudiapermana, Elih (Universitas Negeri Semarang, 2020)
This study aims to describe the character of adolescents in matrilineal care in Minangkabau which is described in seven aspects, namely, religious, disciplined and responsible, independent, creative, respectful and polite, cooperative, and communicative. The population in this study were mothers who have adolescent children, live in Padang city, and have brothers (mamak). The present study used a survey method. A multistage random sampling technique was used for sampling. A sample of 296 respondents was asked to answer a questionnaire. The questionnaire was tested and validated by experts. A descriptive statistical analysis was performed using SPSS. The results showed that the character of respect and manners obtained the highest index score, while the character of cooperation obtained the lowest index score. To improve the character of cooperation, it is necessary to increase the involvement of adolescents in completing a job with their friends and solve their friends' problems.